Kajian Eksperimen Pengaruh Lingkungan Panas Terhadap Suhu Kulit Manusia Menggunakan Fast Response Temperature Probe PS-2135 dan Temperature Array PS-2157 - Kolibu, Hesky Stevy; Suoth, Verna Albert (Sam Ratulangi University, 2019)
Fisika merupakan ilmu alam yang saling berkaitan dengan ilmu lainnya. Salah satu keterkaitannya mempelajari sistem adaptasi tubuh manusia terhadap perubahan suhu. Suhu kulit adalah faktor mendasar dalam pertukaran panas antara tubuh dan lingkungannya. Tingkat suhu kulit secara langsung mempengaruhi transfer energi oleh konveksi dan radiasi dan juga memengaruhi kehilangan panas dari penguapan keringat. Dalam studi eksperimental ini, nilai perubahan suhu kulit dikumpulkan menggunakan Fast Response Temperature Probe PS-2135 dan Temperature Array PS-2157. Tujuan dari studi ini adalah untuk menyelidiki efek dari lingkungan panas pada respon fisiologis suhu kulit tubuhPhysics is a natural science that is interrelated with other sciences. One connection is studying the human body's adaptation system to temperature changes. Skin temperature is a fundamental factor in heat exchanges between the body and its environment. The level of skin temperature directly affects the energy transfer by convection and radiation and also influences heat losses from sweat evaporation. In this experimental study, the skin temperature changes values are collected using Fast Response Temperature Probe PS-2135 and Temperature Array PS-2157. The purpose of this study was to investigate the effects of warm environmental on physiological responses of body skin temperaturePhysics is a natural science that is interrelated with other sciences. One connection is studying the human body's adaptation system to temperature changes. Skin temperature is a fundamental factor in heat exchanges between the body and its environment. The level of skin temperature directly affects the energy transfer by convection and radiation and also influences heat losses from sweat evaporation. In this experimental study, the skin temperature changes values are collected using Fast Response Temperature Probe PS-2135 and Temperature Array PS-2157. The purpose of this study was to investigate the effects of warm environmental on physiological responses of body skin temperature